Hepatitis C–Related Mortality Among American Indian/Alaska Native Persons in the Northwestern United States, 2006-2012. (January 2020) - Hatcher, Sarah M.; Joshi, Sujata; Robinson, Byron F.; Weiser, Thomas
Objective: American Indian and Alaska Native (AI/AN) persons are commonly misclassified in epidemiologic and administrative data sets. The race-corrected hepatitis C virus (HCV)–related mortality rate among AI/AN persons in the Northwest United States (Idaho, Oregon, and Washington State) is unknown. We quantified the disparity in HCV-related mortality between AI/AN persons and non-Hispanic white (NHW) persons in the Northwest during 2006-2012 after correcting misclassified AI/AN race. Methods: After conducting probabilistic record linkage between death records and the Northwest Tribal Registry, we calculated HCV-related mortality rates for AI/AN and NHW persons by using National Center for Health Statistics bridged-race estimates standardized to the US 2000 standard population. Results: The 2006-2012 aggregate age-adjusted HCV-related mortality rate per 100 000 population in the Northwest was 19.6 (95% confidence interval [CI], 17.3-22.2) for AI/AN persons and 5.9 (95% CI, 5.7-6.1) for NHW persons (rate ratio [RR] = 3.3; 95% CI, 3.0-3.8). The disparity was larger among females (RR = 4.6; 95% CI, 3.8-5.5) than among males (RR = 2.9; 95% CI, 2.5-3.4). Conclusion: The disproportionate rate of HCV-related mortality among AI/AN persons in the Northwest highlights the need to expand HCV education, screening, and treatment among this population.